Baited vaccines: A strategy to mitigate rodent‐borne viral zoonoses in humans. (21st June 2018) - Mendoza, Emelissa J.; Warner, Bryce; Kobinger, Gary; Ogden, Nicholas H.; Safronetz, David
Abstract: Rodents serve as the natural reservoir and vector for a variety of pathogens, some of which are responsible for severe and life‐threatening disease in humans. Despite the significant impact in humans many of these viruses, including Old and New World hantaviruses as well as Arenaviruses, most have no specific vaccine or therapeutic to treat or prevent human infection. The recent success of wildlife vaccines to mitigate rabies in animal populations offers interesting insight into the use of similar strategies for other zoonotic agents of human disease. In this review, we discuss the notion of using baited vaccines as a means to interrupt the transmission of viral pathogens between rodent reservoirs and to susceptible human hosts.